Propuesta de áreas de conservación en el Sistema Ibérico Central (España) utilizando la diversidad liquénica. - Burgaz Moreno, Ana Rosa; Martínez Moreno, Isabel; Aragón, Gregorio (Botanica Complutensis, 2001)
MARTÍNEZ, I., ARAGÓN, G. & BURGAZ, A. R. 2001. Proposal of conservation areas in the «Sistema Ibérico Central (Spain)» using lichen diversity. Bot. Complutensis 25: 129-140. Seven forested areas which should be protected in the «Sistema Ibérico Central (Spain)» are proposed. Diversity of epiphytic lichens and presence of species with a very restricted distribution in the Iberian Peninsula has been used to evaluate these areas. A first proposal of ecological stability species in Juniperus thurifera, Pinus nigra and P. sylvestris forests is presented in the Mediterranean Region.